Plan de negocios para la creación de una empresa que presta el servicio de conversión de motos convencionales a híbridas que circulan en la ciudad de Bogotá (2021)
This project consists of carrying out a business plan for the creation of a company to convert conventional to hybrid motorcycles, which circulate in the city of Bogotá DC, the purpose is to install an electric motor on the rear wheel so that can have dual functionality and thus are hybrid. and in the medium term to enter the market of other cities in the country that have a large influx in the acquisition of this type of transport, the main objective is implement of the business plan through a market study that allows us to identify our potential customers through a survey that helps us determine the position of the user regarding the product, with these results we identify the key elements to implement the project and finally carry out a financial study to determine its profitability.